RELIGIOUS AND SOCIAL VALUES IN THE BAJAPUIK TRADITION OF MINANGKABAU WEDDINGS: A COMPARATIVE PERSPECTIVE ON BRIDEWEALTH PRACTICES - Syah, Mhd Asrian; Agustinova, Danu Eko; Arfaton; Rizki, Iqbal Ainur (Balai Penelitian dan Pengembangan Agama Jakarta, 2025)
This study explores the Bajapuik tradition in Minangkabau weddings, focusing on its embedded religious and social values. Specifically, it examines how this tradition fosters inter-family bonds while adapting to the pressures of modernization, including changes in social structure, gender roles, and economic challenges. Using a descriptive qualitative method and historical approach, data were collected through interviews with traditional leaders and cultural observers, as well as direct observation of marriage ceremonies in Pariaman. Findings show that Bajapuik is more than just a ceremonial custom; it reflects core Minangkabau values, including cooperation, family honour, justice, and spirituality. As part of a matrilineal society, the bride’s family offers symbolic respect to the groom’s family, an inversion of most bridewealth practices globally. Although the form and amount of Bajapuik have changed due to external influences and economic conditions, its cultural essence remains strong. Comparatively, Bajapuik shares social functions with mas kawin in Islamic tradition, dowry in South Asia, and bride price in African societies. Despite differences in direction and symbolism, these practices serve to affirm kinship ties, reinforce social status, and embody shared cultural values.